Pest categorisation of Matsucoccus massonianae - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2022)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Matsucoccus massonianae (Hemiptera: Matsucoccidae), the Massonian pine bast scale, for the EU territory. M. massonianae occurs in western China and has been reported as a pest of Pinus massoniana (Chinese red pine) and P. thunbergii (Japanese black pine). These hosts occur in the EU as ornamental/amenity trees. Other scales in the Matsucoccus genus feed on a variety of Pinus species and the host range of M. massonianae could be wider than is currently recorded. There is one generation per year. All stages occur on the branches and stems of hosts with developing nymphs and adult females feeding under the bark on the phloem vessels of the host. Symptoms include the yellowing/browning of host needles, early needle drop, desiccation of shoots and bark necrosis. The most serious infestations occur in hosts aged 8–25 years old and there can be some host mortality. In principle, host plants for planting and plant products such as cut branches and wood with bark could provide entry pathways into the EU. However, prohibitions on the import of Pinus from non‐European third countries close these pathways. In China, M. massonianae occurs in regions with temperate humid conditions and hot summers. These conditions are also found in parts of southern EU. Were M. massonianae to establish in the EU, it is conceivable that it could expand its host range; however, this remains uncertain. M. massonianae satisfies all the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest. Some uncertainty exists over the magnitude of potential impacts.